«Una fantasia per dire di un’invenzione». Raccontando Istinto di morte e conoscenza - Fagioli, Massimo (Il sogno della farfalla, 2022)
On several occasions Massimo Fagioli recounted the human and intellectual journey that led him into the writing of Death instinct and knowledge. On the 50th anniversary of the first edition, this anthology brings together some extracts from his public speeches and lessons. The most fundamental concepts and terms of the Human Birth Theory such as non-conscious thought, disappearance phantasy and annulment pulsion are investigated and explored through the author’s words.